Perancangan dan Pembuatan Website pada Komunitas Discerning Universitas Kristen Petra - Lawalata, Imanuel Friendly; Wibowo, Adi; Setiawan, Alexander (Jurnal Infra, 2014)
The advancement of technology today has helped the widespread of internet among ordinary people in the society. The promotion of various goods, service, and information could be done easily using the internet. Internet is also easily accessible and usable anywhere, as long as the network is available.Inspired by the concern of the students involved in the campus ministry, a community is formed to bring about a positive cultural change in Petra Christian University. The philosophy of the community is to be a community of a disciples of Jesus, concerned in worlds problems, longing to bring Gods transformation. The community is called